PENGARUH MOTIVASI, KOMUNIKASI DAN STRES KERJA TERHADAP KEPUASAN KERJA KARYAWAN HOTEL BATIQA BANDAR LAMPUNG - Rika Fatmala Putri; Hepiana Patmarina (STIE Wiyatamandala, 2023)
This research was conducted to determine the effect of motivation, communication and work stress on employee job satisfaction at Hotel Batiqa Bandar Lampung. The population for this study were all permanent employees of Hotel Batiqa Bandar Lampung who worked at the company and totaled 43 people. The sample used in this study used a non-probability sampling technique with saturated sampling. All members of the population will be used as research samples, amounting to 43 respondents. Data was collected by questionnaire and documentation method. This study analyzed data by means of descriptive analysis, validity test, reliability test, multiple linear regression analysis, coefficient of determination test, and hypothesis testing. Researchers used SPSS software version 22 as a tool for data analysis. The results showed that each of the motivational and communication variables partially had a positive effect on employee job satisfaction at Hotel Batiqa Bandar Lampung, but on the job stress variable partially it had no effect on employee job satisfaction at Hotel Batiqa Bandar Lampung. This study also shows that motivation, communication and work stress simultaneously influence the job satisfaction of Hotel Batiqa Bandar Lampung employees.